Extended spectrum beta lactamase producing organisms causing urinary tract infections in Sri Lanka and their antibiotic susceptibility pattern –A hospital based cross sectional study. Issue 1 (December 2017) - Fernando, M.; Luke, W.; Miththinda, J.; Wickramasinghe, R.; Sebastiampillai, B.; Gunathilake, M.; Silva, F.; Premaratna, R.
Abstract Background Extended Spectrum Beta- Lactamase producing organisms causing urinary tract infections (ESBL-UTI) are increasing in incidence and pose a major burden to health care. While ESBL producing Klebsiella species seem to account for most nosocomial outbreaks, ESBL-producingE. coli have been isolated from both hospitalized and non-hospitalized patients. Although 95-100% ESBL organisms are still considered sensitive to meropenem, rapid emergence of carbapenem resistance has been documented in many countries. The objective of this study was to evaluate urinary tract infections caused by ESBL producers and the antibiotic susceptibility patterns in Sri Lanka. Methods Patients with confirmed ESBL-UTI admitted to Professorial Medical Unit, Colombo North Teaching Hospital from January – June 2015 were recruited to the study. Their urine culture and antibiotic susceptibility reports were evaluated after obtaining informed written consent. Results Of 61 culture positive ESBL-UTIs, E. coli caused 53 (86.8%), followed by Klebsiella in 8 (13.1%).30 (49.1%) had a history of hospitalization within the past three months and included 6/8(75%) of Klebsiella UTI and 24/53(45.2%) ofE.coli UTI. Antibiotic susceptibility of ESBL organisms were; Meropenem 58 (95%), Imipenem 45 (73.7%), Amikacin 37 (60.6%) and Nitrofurantoin 28(45.9%). In 3(4.9%), E.coli were resistant to Meropenem. These three patients had received multiple antibiotics including meropenem in the recent past for recurrent UTI. Conclusions We observed a higher percentage ofE. coli over Klebsiella as ESBL producing organisms suggesting most ESBL-UTIs to be community acquired, Carbapenems seem to remain as the first line therapy for majority of ESBL-UTIs in the local setting. However 4.9% prevalence of meropenem resistance is alarming compared to other countries. Although prior antibiotic utilization and hospitalization may contribute to emergence of ESBL producing Klebsiella andE.coli in Sri Lanka, high prevalence of community acquired ESBL-E. coli needs further investigations to identify potential causes . Being a third world country with a free health care system, observed alarming rate of carbapenem resistance is likely to add a significant burden to health budget. We feel that treatment of infections in general needs a careful approach adhering to recommended antibiotic guidelines in order to prevent emergence of multi drug resistant organisms.